Thalamic T-Type Ca2+ Channels Mediate Frontal Lobe Dysfunctions Caused by a Hypoxia-Like Damage in the Prefrontal Cortex - Kim, Jeongjin; Woo, Jeonghoon; Park, Young-Gyun; Chae, Sujin; Jo, Seonmi; Choi, Jeong Woo; Jun, Hong Young; Yeom, Young Il; Park, Seong Hoon; Kim, Kyung Hwan; Shin, Hee-Sup; Kim, Daesoo (SOC NEUROSCIENCE, 2011)
Hypoxic damage to the prefrontal cortex (PFC) has been implicated in the frontal lobe dysfunction found in various neuropsychiatric disorders. The underlying subcortical mechanisms, however, have not been well explored. In this study, we induced a PFC-specific hypoxia-like damage by cobalt-wire implantation to demonstrate that the role of the mediodorsal thalamus (MD) is critical for the development of frontal lobe dysfunction, including frontal lobe-specific seizures and abnormal hyperactivity. Before the onset of these abnormalities, the cross talk between the MD and PFC nuclei at theta frequencies was enhanced. During the theta frequency interactions, burst spikes, known to depend on T-type Ca2+ channels, were increased in MD neurons. In vivo knockout or knockdown of the T-type Ca2+ channel gene (Ca(V)3.1) in the MD substantially reduced the theta frequency MD-PFC cross talk, frontal lobe-specific seizures, and locomotor hyperactivity in this model. These results suggest a two-step model of prefrontal dysfunction in which the response to a hypoxic lesion in the PFC results in abnormal thalamocortical feedback driven by thalamic T-type Ca2+ channels, which, in turn, leads to the onset of neurological and behavioral abnormalities. This study provides valuable insights into preventing the development of neuropsychiatric disorders arising from irreversible PFC damage.
Keywords: DEFICIT HYPERACTIVITY DISORDER; ATTENTION-DEFICIT/HYPERACTIVITY DISORDER; CORTICALLY GENERATED SEIZURES; TRAUMATIC BRAIN INJURY; SPIKE-WAVE COMPLEXES; THALAMOCORTICAL RELAY; CALCIUM-CHANNELS; ABSENCE SEIZURES; FAST COMPONENTS; EARLY-CHILDHOOD